Fabrication of a novel composite gel bead to reclaim methyl orange from a binary dye mixture: An active role of adsolubilization phenomenon. (December 2022) - Biswas, Subhadeep; Pal, Anjali
Abstract: The present work demonstrates a novel protocol in accordance with the reduce, reuse, and recycle principle of waste management rules for dye wastewater treatment as well as selective extraction of desired dye. Here two model dyes viz., methyl orange (MO) (an anionic dye) and methylene blue (MB) (a cationic dye) have been considered as the components of dye wastewater, and alginate-xanthan (Alg-Xan) biopolymer composite hydrogel beads modified with a cationic surfactant such as cetylpyridinium chloride (CPC), as the sorbent material. CPC bilayers on Alg-Xan composite surface showed excellent MO uptake performance (>85–90%) via adsolubilization when the MO is present alone or in a binary mixture with MB. On the other hand, MB got partially transferred (∼30–50%) to the solid surface through diffusion phenomenon both in the presence (∼50%) and absence (∼30%) of MO. After the accumulation of the dye molecules, MO can be easily reclaimed (>90%) using 1-butanol as the extracting solvent; however, no detachment of MB from the solid surface takes place. The stability and suitability of the hydrogel beads were investigated under different operating conditions. Furthermore, Alg-Xan-CPC composite beads have been characterized using FTIR, SEM analysis, and particle size distribution. The newly developed Alg-Xan-CPC composite beads show good reusability up to four cycles and they perform well in real wastewater (∼95% recovery of MO). The novelty of the current research includes the synthesis of a CPC micelle anchored biopolymer adsorbent, which is capable of attracting both the cationic and anionic dyes from water bodies, followed by extractive reclamation of the anionic dye only. The application of biopolymers for wastewater treatment and resource recovery from the waste stream is undoubtedly a sustainable environmental remediation option. Hence, this research work is expected to present a novel application of biopolymers for dye wastewater mitigation as well as reclamation of desired useful dye. Graphical Abstract: ga1